2015
DOI: 10.1007/s00417-014-2899-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute central serous chorioretinopathy: a correlation study between fundus autofluorescence and spectral-domain OCT

Abstract: The simultaneous acquisition of FAF and SD-OCT provides detailed findings of retinal abnormalities of CSCR and may help to understand the evolving process linked to CSCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 48 publications
2
34
0
3
Order By: Relevance
“…Focal areas of hypo-autofluorescence at the level of the leakage points are indeed observed in 70e100% of eyes with acute CSCR (Fig. 2D), which supports the hypothesis of a focal RPE defect or detachment of RPE cells at this site (Ayata et al, 2009;Eandi et al, 2005;Iacono et al, 2015;. In recurrent CSCR, the leakage point is usually different from previous episodes but locates in the vicinity of the first one, reflecting a barrier weakness persisting in this area.…”
Section: Fundus Autofluorescencesupporting
confidence: 74%
See 3 more Smart Citations
“…Focal areas of hypo-autofluorescence at the level of the leakage points are indeed observed in 70e100% of eyes with acute CSCR (Fig. 2D), which supports the hypothesis of a focal RPE defect or detachment of RPE cells at this site (Ayata et al, 2009;Eandi et al, 2005;Iacono et al, 2015;. In recurrent CSCR, the leakage point is usually different from previous episodes but locates in the vicinity of the first one, reflecting a barrier weakness persisting in this area.…”
Section: Fundus Autofluorescencesupporting
confidence: 74%
“…It may either return to normal, as observed in a majority of cases after SRD resolution (Iacono et al, 2015), or be progressively replaced by an increased FAF, as observed in episodes persisting more than 4 months (Framme et al, 2005). While the masking produced by the SRD and the elongated photoreceptor outer segments could explain the initial decrease in FAF (Fig.…”
Section: Fundus Autofluorescencementioning
confidence: 90%
See 2 more Smart Citations
“…During the initial presentation of CSCR, 72–96 % of cases show hypo-autofluorescence corresponding to the focal leakage site on fluorescein angiogram and to the area of serous retinal detachment, due to blockage by subretinal fluid [111113]. A subset of patients may show localized RPE detachment, corresponding with focal hyper-autofluorescence.…”
Section: Central Serous Chorioretinopathymentioning
confidence: 99%